Identification of a Carboxylic Acid Metabolite from the Catabolism of Fluoranthene by a Mycobacterium sp - Kelley, Ingrid (1991)
A Mycobacterium sp. previously isolated from oil-contaminated estuarine sediments was capable of extensively mineralizing the high-molecular-weight polycyclic aromatic hydrocarbon fluoranthene. A carboxylic acid metabolite accumulated and was isolated by thin-layer and high-pressure liquid chromatographic analyses of ethyl acetate extracts from acidified culture media. The metabolite reached a maximum concentration of approximately 0.65% after 24 h of incubation. On the basis of comparisons with authentic compound in which we used UV and fluorescence spectrophotometry and R(f) values, as well as mass spectral and proton and carbon nuclear magnetic resonance spectral analyses, the metabolite was identified as 9-fluorenone-1-carboxylic acid. This is the first report in a microbial system of a fluoranthene metabolite in which significant degradation of one of the aromatic rings has occurred.